Training For Undergraduate Research: A Bimodal Experience With Edmodo at Universidad Nacional Experimental Simón Rodríguez, núcleo Barquisimeto (Ágora de Heterodoxias, 2019)
The incorporation of Information and Communication Technologies (ICT) is a necessary step in the intention to offer an education with relevant and vanguard features. In this sense, at the university level, the results advance towards the development of blended experiences in a previous preparation, monitoring and reflection about the results. In this line of thought, a bimodal training intervention developed with the Edmodo educational social network is detailed for the Project II course of the academic period 2018-I, belonging to the curriculum of the Bachelor's Degree in Administration and Bachelor's Degree in Education at the Experimental National Simón Rodríguez University, Barquisimeto Extension. The methodological design used focused on the perspective of action research in the classroom, following the diagnostic phases, planning, action and reflection. After the evaluation of the experience, a high participation was demonstrated during the weeks of virtual work, therefore, the interaction with didactic purposes was not limited exclusively to face-to-face meetings. In addition, according to the testimonies of the participants, the socialization of the activities fostered the interest and the feedback about the advances of the research proposal among peers, which allowed a configuration of the process of learning to investigate from a collaborative perspective and not as a know-do alone.
Keywords: training of researchers; undergraduate; bimodality; virtual platform; Edmodo